Republic of Turkey (Washington, D.C.)
1 mikrofiş (1. eser (4 poz ; 4 sayfa), 2. eser (poz 5-9 ; 6 sayfa), 3. eser (poz 10-12 ; 3 sayfa)
Keywords: Concerns the importation and distribution of pharmaceutical and medical preparations in Turkey.